Fostering plant awareness through lesson study: Participatory action research with science teachers - Indra Fardhani; Yayuk Mulyati; Dian Nugraheni; S. Sugiyanto; Rini Anggi Arista; Eka Nurul Qomaliyah; Imam Syamsuddi; Ikrar Riyas Mutawaqil Yasin; Umi Fitriyati; Khalifatulloh Fiel’ardh (Universitas Muhammadiyah Malang, 2026)
Background-Empirical studies that integrate plant awareness into non-botany science topics through lesson study are still limited, particularly in the Indonesian educational context. Objective-This study investigates junior high school science teachers' plant awareness and explores the integration of plant-related content through lesson study to address plant awareness disparity. Method-Conducted with 23 science teachers from the Musyawarah Guru Mata Pelajaran IPA in East Java, Indonesia, the research employed a participatory action research framework. Data were collected via questionnaires, focus group discussions, and observations of lesson study cycles. Results-Findings revealed a disparity in teachers' plant awareness: while they exhibited positive interest and attitudes towards plants, their visual perception often relegated plants to a background role. Furthermore, a significant portion (39.1%) lacked a clear understanding of plant awareness. Through collaborative lesson study, teachers developed and implemented two innovative lesson plans: integrating medicinal plants (jamu making) into the human digestive system topic and using plants as objects for length measurement in physics. Conclusion-The study concludes that while teacher awareness and curriculum representation of plants need improvement, lesson study provides an effective collaborative model for developing engaging, integrative lessons that can help combat plant awareness disparity among students.